فاعلية القائم بالإتصال في ترقية الصورة الذهنية للمؤسسة دراسة حالة إذاعة الجزائر من مسيلة - رقيق منار (جامعة محمد بوضياف –المسيلة-, 2025)
جاءت دراستنا هذه لمعرفة دور القائم بالاتصال في تحسين الصورة الذهنية لإذاعة الجزائر من المسيلة ولضبط هذه الدراسة حاولت الاجابة عن التساؤل الرئيسي: فيما يتمثل دور القائم بالإتصال في ترقية الصورة الذهنية لإذاعة الجزائر من مسيلة. حيث اتسمت هذه الدراسة إلى تحقيق أهداف نذكر منها: التعرف على واقع الاتصال في إذاعة الجزائر من مسيلة، الكشف عن الدور الذي يقوم به القائم بالاتصال من أجل تحسين صورة المؤسسة، الوصول الى الكيفية التي من خلالها يتمكن القائم بالاتصال من تحسين صورة إذاعة الجزائر من مسيلة. واعتمدنا لمعالجة هذا الموضوع منهج دراسة الحالة و الإستبيان والملاحظة والمقابلة لجمع وتفريغ البيانات حيث استخلص من هذه الدراسة أن القائم بالاتصال له دور كبير في تحسين صورة إذاعة الجزائر من مسيلة فهو همزة وصل بينها وبين جمهورها وكنتائج فرعية توصلنا الى أن بيئة الاتصال المؤسسية تسهم بشكل كبير في تعزيز الأداء الوظيفي للقائمين بالإتصال عبر زيادة الإبداع ، واعتماد المؤسسة بدرجة كبيرة على جهود القائمين بالإتصال واستخدام الوسائل الحديثة لتعزيز صورتها الإيجابية ويواجه أحيانا بعض الصعوبات أكثرها تنظيمية لكنه سرعان من يعمل على حلها وحل المشاكل التي تعترض الجمهور. This study aims to understand the role of the communicator in improving the image of Radio Algeria from M'sila. To address this issue, I attempted to answer the main question: What is the role of the communicator in promoting the image of Radio Algeria from M'sila? This study aimed to achieve several objectives, including: identifying the reality of communication at Radio Algeria from M'sila; revealing the role played by the communicator in improving the institution's image; and determining how the communicator can improve the image of Radio Algeria from M'sila. To address this issue, we adopted a case study approach, including questionnaires, observation, and interviews to collect and transcribe data. This study concluded that the communicator plays a significant role in improving Radio Algeria from M'sila's image, as he serves as a link between the institution and its audience. As secondary findings, we concluded that the institutional communication environment contributes significantly to enhancing the job performance of communicators by increasing creativity. The institution relies heavily on the efforts of communicators and the use of modern means to enhance its positive image. While communicators sometimes face difficulties, most of which are organizational, they quickly work to resolve them and address the problems facing the public.